The role of cognitive and social leisure activities in dementia risk: assessing longitudinal associations of modifiable and on-modifiable risk factors. (11th January 2022) - Duffner, L. A.; Deckers, K.; Cadar, D.; Steptoe, A.; de Vugt, M.; Köhler, S.
Abstract: Aims: With the projected surge in global dementia cases and no curative treatment available, research is increasingly focusing on lifestyle factors as preventive measures. Social and cognitive leisure activities are promising targets, but it is unclear which types of activities are more beneficial. This study investigated the individual and joint contribution of cognitive and social leisure activities to dementia risk and whether they modify the risks associated with other potentially modifiable and non-modifiable risk factors. Methods: We used data from the English Longitudinal Study of Ageing (ELSA) from 7917 participants, followed up from 2008/2009 (Wave 4) until 2018/2019 (Wave 9) for incident dementia. Self-reported baseline cognitive activities (e.g. 'reading the newspaper'), the number of social memberships (e.g. being a member of a social club) and social participation (e.g. 'going to the cinema') were clustered into high and low based on a median split. Subsequently, their individual and joint contribution to dementia risk, as well as their interaction with other dementia risk factors, were assessed with Cox regression models, adjusting for age, sex, level of education, wealth and a composite score of 11 lifestyle-related dementia risk factors. Results: After a median follow-up period of 9.8 years, the dementia incidence rate was 54.5 cases per 10.000 person-years (95% CI 49.0–60.8). Adjusting for demographic and other lifestyle-related risk factors, higher engagement in cognitive activities (HR = 0.58; 95% CI 0.40–0.84), a greater number of social memberships (HR = 0.65; 95% CI 0.51–0.84) and more social participation (HR = 0.71; 95% CI 0.54–0.95) were associated with lower dementia risk. In a joint model, only engagement in cognitive activities (HR = 0.60; 95% CI 0.40–0.91) and social memberships (HR = 0.75; 95% CI 0.56–0.99) independently explained dementia risk. We did not find any interaction with other modifiable and non-modifiable risk factors. Conclusions: Engagement in cognitive and social leisure activities may be beneficial for overall dementia risk, independent of each other and other risk factors. Both types of activities may be potential targets for dementia prevention measures and health advice initiatives.